International Environmental Agreements for River Sharing Problems - Harold Houba; Gerard van der Laan; Yuyu Zeng (Tinbergen Institute, 2013)
We study coalition formation and the strategic timing of membership of an IEA for environmental issues in the Coalitional Bargaining Game (CBG) of Gomes 2005, Econometrica). For the general CBG, we derive the necessary and sufficient condition for immediate formation of the grand coalition. We apply the CBG to a river sharing problem with two symmetric upstream agents and one downstream agent. Taking the discount factor and a productivity variable of water as parameters, we identify five regions in the parameter space. First, there is a region in which the grand coalition always forms immediately. Second, there are two regions in which there is for sure gradual coalition formation, in one of these regions there is a positive probability that the upstream agents form a monopoly. Third, there are two regions in which the grand coalition forms immediately with positive probability, but also gradual coalition formation might occur with positive probability.
Keywords: C78; Q25; 330; Coalitional Bargaining Game; International Environmental Agreements; River Sharing Problems; Markov Perfect Equilibrium; Efficiency; Monopoly